Investigating EFL Students’ Perception on The Use of Digital Storytelling (DST) In Learning to Speak English - Wati, Atikah; Anita; Yulianawati, Ida (ENGLISH JOURNAL OF INDRAGIRI, 2026)
The aim of this study was to investigate how EFL students saw the application of Digital Storytelling (DST) as a means to support their English. The aims are to establish the advantages of the application of Digital Storytelling (DST) at school and to examine how the students view DST as a way of supporting their speaking. The study is conducted at SMAN 1 Sindang, Indramayu, involving 44 senior high school participants. For the sake of obtaining overall data, a mixed method was utilized through the use of questionnaires and semi-structured interviews. The results indicated that students have positive attitudes towards DST, demonstrating how DST makes them more motivated, creative, and confident in delivering their messages in English. In addition to encouraging learners to become active in studying, DST is a great avenue for fluency, pronunciation, and vocabulary practice. However, it was also mentioned that some of the issues were quoted, such as a lack of technical knowledge and a shortage of resources. The significance of the findings is the potential of DST as an effective pedagogical instrument that integrates technology application and language learning. The implication of the study is that DST is effective in developing student engagement and speaking skills. Further research is recommended to investigate its long-term impact and explore its application in other language skills and educational environments.